Response of inflorescence structure and oil yield components to source-sink manipulation by artificial shading in olive - Trentacoste, Eduardo Rafael (2022)
Olive yield components are first determined during flowering, ovary growth, and fruit set. However, variations of the assimilates available during these important processes have been little studied. The aims of this study were to evaluate the effects of source-sink alterations on (i) production of flowers and their structure, (ii) sink responsiveness source activity, and (iii) the relationship between final fruit mass and flower ovary size. Two levels of shading at 50% and 80% were applied in an orchard cv. Arbequina over three seasons, with two durations: short-period (SP, from harvest up to 20 days after flowering) and long-period (LP, continuous shading from beginning to end of the experimental period). An unshaded Control was included. Control presented the highest fruit yield and was 50% greater than both SP50-LP50, and 80% greater than both SP80-LP80. Fruit number was highly responsive to source-sink alterations. The control and both SP50-LP50 treatments presented similar fruit loads, whereas both SP80-LP80 produced 80% less fruits. Source activity alteration during pre-fruit set affected inflorescence structure. By contrast, during the post-fruit set, it drastically reduced inflorescence production. Fruit mass increased mainly due to fruit growth rate in relation to the assimilate. Reduction in ovary mass due to low source activity during pre-fruit set had a slight influence on final fruit mass when source activity was not limited during the post-fruit set period. Fruit oil concentration was highly conservative across a wide range of source-sink ratios.